The Relationship between Nurse's Characteristics and Motivation with the Implementation of International Patient Safety Goal - Nurhanifah Nurhanifah; Hajjul Kamil; Syahrul Syahrul; Marlina Marlina; Dewi Marianthi (Media Karya Kesehatan, 2021)
Patient safety is a mandatory requirement that must be implemented in all hospitals and is one of the efforts in implementing International Patient Safety Goals (IPSG). The study aims to determine the relationship between nurses' characteristics and motivation with the implementation of IPSG in Inpatient Rooms at Aceh Government Hospital. This study was a quantitative study with cross-sectional study design. The total samples were 122 nurses which were selected through a simple random sampling method. Data was collected using a questionnaire consisted of respondent's characteristics, the implementation of IPSG,  and motivation aspect using The Unified Motivation Scales (UMS). Data were analyzed using descriptive statistical tests and nonparametric inferential statistical tests; chi-square and logistic regression test. This study found that there was no relationship between age, gender, marital status with the implementation of IPSG. Education, employment status, length of work, and motivation have relations with IPSG. Education with odds ratio = 33.469 and the need for achievement with odds ratio = 9.669 were the sub-variables that were significantly related to the implementation of IPSG in Inpatient Rooms at Aceh Government Hospital. Base on the result, it can be concluded that the nurses' characteristics of education and the need for achievement were the most significant predictors related to the implementation of IPSG in the Inpatient Rooms at Aceh Government Hospital.  Implementing IPSG in the Aceh Hospital Inpatient Room can be continuously improved by always motivating nurses, providing rewards, and encouraging an attitude of need for achievement, affiliation and need for power.Keywords: Implementation, IPSG, Motivation, Nurse.